Hilirisasi Teknologi Budar Ramah Lingkungan Berbasis Sumberdaya Lokal Untuk Meningkatkan Hasil Tangkapan Ikan Dan Mengurangi Destructive Fishing Nelayan Tradisional Meureubo - Muhammad Rizal; Afdhal Fuadi (Marine Kreatif, 2026)
The small-scale fishing grounds of Meureubo Village operate only in coastal waters up to 12 nautical miles out, using a relatively small fleet of vessels under 5 GT. This fleet size is relatively small compared to the fleets larger than 5 GT that can reach fishing grounds in the Indian Ocean. The fishing gear used is a trammel net or green bottom gill net to catch demersal fish, so that the fish caught are relatively small and many of the catches are bycatch. Based on these problems, environmentally friendly fishing gear is needed with the target of catching high-value demersal fish, namely BuDar (Bottom Trap) technology. The purpose of this activity is to improve the knowledge and skills of the Independent Fishermen's Cooperatives (KUB) and Fishermen's Wives Cooperatives (KUB) in Meureubo Village. The implementation method is through outreach, training, and mentoring. The implementation of activities includes providing outreach and education, training, and monitoring the results of the activities. The monitoring and evaluation results showed a 75% increase in knowledge among the Independent Fishermen's Business Group (KUB) and 80% among the Fishermen's Wives' Business Group (KUB). Furthermore, skills also increased by 85% among the Independent Fishermen's Business Group (KUB), while skills also increased by 85%.